Diffusion-Weighted Imaging–Detected Ischemic Lesions following Endovascular Treatment of Cerebral Aneurysms: A Systematic Review and Meta-Analysis - Bond, K.M.; Brinjikji, W.; Murad, M.H.; Kallmes, D.F.; Cloft, H.J.; Lanzino, G. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Endovascular treatment of intracranial aneurysms is associated with the risk of thromboembolic ischemic complications. Many of these events are asymptomatic and identified only on diffusion-weighted imaging. We performed a systematic review and meta-analysis to study the incidence of DWI positive for thromboembolic events following endovascular treatment of intracranial aneurysms.MATERIALS AND METHODS: A comprehensive literature search identified studies published between 2000 and April 2016 that reported postprocedural DWI findings in patients undergoing endovascular treatment of intracranial aneurysms. The primary outcome was the incidence of DWI positive for thromboembolic events. We examined outcomes by treatment type, sex, and aneurysm characteristics. Meta-analyses were performed by using a random-effects model.RESULTS: Twenty-two studies with 2148 patients and 2268 aneurysms were included. The overall incidence of DWI positive for thromboembolic events following endovascular treatment was 49% (95% CI, 42%–56%). Treatment with flow diversion trended toward a higher rate of DWI positive for lesions than coiling alone (67%; 95% CI, 46%–85%; versus 45%; 95% CI, 33%–56%; P = .07). There was no difference between patients treated with coiling alone and those treated with balloon-assisted (44%; 95% CI, 29%–60%; P = .99) or stent-assisted (43%; 95% CI, 24%–63%; P = .89) coiling. Sex, aneurysm rupture status, location, and size were not associated with the rate of DWI positive for lesions.CONCLUSIONS: One in 2 patients may have infarcts on DWI following endovascular treatment of intracranial aneurysms. There is a trend toward a higher incidence of DWI-positive lesions following treatment with flow diversion compared with coiling. Patient demographics and aneurysm characteristics were not associated with DWI-positive thromboembolic events.